2012
DOI: 10.1088/0965-0393/20/2/024003
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent estimate for linear viscoelastic polycrystals with internal variables inferred from the collocation method

Abstract: Abstract.The correspondence principle is customarily used with the Laplace-Carson transform technique to tackle the homogenization of linear viscoelastic heterogeneous media. The main drawback of this method lies in the fact that the whole stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Finally, it can be also noted that the agreement between the FFT and the collocation results, at both moderate and high contrast, confirms the accuracy of the collocation method, as is documented in the literature (see, for instance, Brenner et al, 2002;Rekik and Brenner, 2011;Vu et al, 2012).…”
Section: Granular Two-phase Compositessupporting
confidence: 82%
See 2 more Smart Citations
“…Finally, it can be also noted that the agreement between the FFT and the collocation results, at both moderate and high contrast, confirms the accuracy of the collocation method, as is documented in the literature (see, for instance, Brenner et al, 2002;Rekik and Brenner, 2011;Vu et al, 2012).…”
Section: Granular Two-phase Compositessupporting
confidence: 82%
“…However, the present results apply to more general situations as will be illustrated below (see also Vu et al, 2012, Appendix A).…”
Section: Restrictions On Prony Seriesmentioning
confidence: 63%
See 1 more Smart Citation
“…Ricaud and Masson (2009) showed that for specific microstructures (two-phase composites whose overall elastic properties are given by one of the Hashin-Shtrikman bounds) the relaxation spectrum of the composites remains discrete. This implies (Ricaud and Masson, 2009;Vu et al, 2012) that the overall constitutive relations of such composites can be alternatively written with a finite number of internal variables. Conversely for composites with a continuous relaxation spectrum, an infinite number of internal variables is required and the advantage of an analytical model for subsequent use in a macroscopic numerical computation is lost.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely for composites with a continuous relaxation spectrum, an infinite number of internal variables is required and the advantage of an analytical model for subsequent use in a macroscopic numerical computation is lost. This has motivated the introduction of approximate models with a finite number of internal variables (or equivalently with a finite number of relaxation times) mostly based on the approximation of the continuous relaxation spectrum by Prony series (Rekik and Brenner, 2011;Vu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%